2016
DOI: 10.1021/acs.inorgchem.6b00891
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Two-Photon Lanthanide Bioprobes Able to Accumulate in Live Cells

Abstract: An original cationic water-soluble cyclen-based Eu(III) complex [EuL(1)](+) featuring a chromophore-functionalized antenna to increase the two-photon (2P) absorption properties was synthesized. The photophysical properties were thoroughly studied in various solvents and rationalized with the help of theoretical calculations. The complex exhibits an optimized 2P absorption cross section. Finally, 2P microscopy imaging experiments on living T24 human cancer cells highlighted the spontaneous internalization and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 22 publications
(24 reference statements)
2
51
1
Order By: Relevance
“…These two parameters are qualitative indicators of the symmetry of the coordination polyhedron. Comparison with similar parameters in other macrocyclic complexes featuring similar antennas confirmed that they are lower than that of the C 3 symmetric tacn based complex (r=10.9, R 2 =79 %) but compare well with those of C 2 diMe‐cyclen [Eu L 1b ] + (r=2.5, R 2 =56 %) and distorted C 3 pyclen derivatives (r=3.0, R 2 =65 %) . Contrarily to what we observed at 77 K, at room temperature the J=0 transition of [Eu L 2b ] + presents two components at 581 (main peak B, Figure ) and 580.1 nm (minor peak A, Figure ) signature of the presence of at least two different emitting species.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…These two parameters are qualitative indicators of the symmetry of the coordination polyhedron. Comparison with similar parameters in other macrocyclic complexes featuring similar antennas confirmed that they are lower than that of the C 3 symmetric tacn based complex (r=10.9, R 2 =79 %) but compare well with those of C 2 diMe‐cyclen [Eu L 1b ] + (r=2.5, R 2 =56 %) and distorted C 3 pyclen derivatives (r=3.0, R 2 =65 %) . Contrarily to what we observed at 77 K, at room temperature the J=0 transition of [Eu L 2b ] + presents two components at 581 (main peak B, Figure ) and 580.1 nm (minor peak A, Figure ) signature of the presence of at least two different emitting species.…”
Section: Resultssupporting
confidence: 84%
“…A value of 0.2 was obtained for [Eu L 2b ] + similar to that of the parent complex (q=0.25–0.35 for [Eu L 2a ] + ) and 0.1 for [Yb L 2c ] + . Interestingly, these values are lower than that of their diMe‐cyclen analogues (0.5 and 0.2 for [Eu L 1b ] + and [Yb L 1c ] + , respectively) suggesting that the more sterically constrained cross‐bridged cyclam scaffold offers a stronger protection against water coordination ( vide infra ). This conclusion is further corroborated by longer lifetimes observed in water for the cb‐cyclam based complexes compared to their diMe‐cyclen analogues and the six‐fold increase of the quantum yield measured for [Eu L 2b ] + (0.06 vs 0.01 for [Eu L 1b ] +[7g] ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[60] Fig. 12 Schematic mechanism of single and two--photon excitation Various examples of europium complexes for two--photon applications have been reported so far, [61], [62], [63] including bright alkynyl--pyridine systems, functionalised with hydrophilic groups (PEG, sulfo--betaine, carboxylic acids) to ensure water solubility and cellular permeabilisation. Unfortunately, the relatively low two--photon cross--sections (<100 GM) of these systems require the use of rather high energy excitation sources that may result in lower signal intensity compared to organic dyes, such as the series of squaraine--rotaxane derivatives (up to 10,000 GM).…”
Section: Two--photon Excitationmentioning
confidence: 99%